Brief Report: Whole‐Exome Sequencing to Identify Rare Variants and Gene Networks That Increase Susceptibility to Scleroderma in African Americans. Issue 10 (29th August 2018) - Gourh, Pravitt; Remmers, Elaine F.; Boyden, Steven E.; Alexander, Theresa; Morgan, Nadia D.; Shah, Ami A.; Mayes, Maureen D.; Doumatey, Ayo; Bentley, Amy R.; Shriner, Daniel; Domsic, Robyn T.; Medsger, Thomas A.; et al.
Abstract : Objective: Whole‐exome sequencing (WES) studies in systemic sclerosis (SSc) patients of European American (EA) ancestry have identified variants in the ATP8B4 gene and enrichment of variants in genes in the extracellular matrix (ECM)–related pathway that increase SSc susceptibility. This study was undertaken to evaluate the association of the ATP8B4 gene and the ECM‐related pathway with SSc in a cohort of African American (AA) patients. Methods: SSc patients of AA ancestry were enrolled from 23 academic centers across the US under the Genome Research in African American Scleroderma Patients consortium. Unrelated AA individuals without serologic evidence of autoimmunity who were enrolled in the Howard University Family Study were used as unaffected controls. Functional variants in genes reported in the 2 WES studies in EA patients with SSc were selected for gene association testing using the optimized sequence kernel association test (SKAT‐O) and pathway analysis by Ingenuity Pathway Analysis in 379 patients and 411 controls. Results: Principal components analysis demonstrated that the patients and controls had similar ancestral backgrounds, with roughly equal proportions of mean European admixture. Using SKAT‐O, we examined the association of individual genes that were previously reported in EA patients and none remained significant, including ATP8B4 ( P = 0.98). However, we confirmed the previously reported association of the ECM‐related pathway with enrichment of variants within the COL13A1, COL18A1, COL22A1, COL4A3, COL4A4, COL5A2, PROK1, and SERPINE1 genes (corrected P = 1.95 × 10 −4 ). Conclusion: In the largest genetic study in AA patients with SSc to date, our findings corroborate the role of functional variants that aggregate in a fibrotic pathway and increase SSc susceptibility.